2007
DOI: 10.1002/dvg.20280
|View full text |Cite
|
Sign up to set email alerts
|

Larval legs of mulberry silkworm Bombyx mori are prototypes for the adult legs

Abstract: Morphological diversity of leg appendages is one of the hallmarks of developmental evolution. Limbs in insects may develop either from their embryonic prototypes or from imaginal discs harbored inside the larva. Bombyx mori (B. mori), a Lepidopteran insect, develops adult wings from larval wing imaginal discs. However, it has been debated whether the adult legs of B. mori arise from imaginal discs or from the larval legs. Here we addressed how the larval legs relate to their adult counterparts. We present the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The Y‐shaped thoracic legs were reminiscent of a similar biramous phenotype observed in delta RNAi embryos of cricket (Kainz et al, ; Mito et al, ). In normal silkworms, thoracic legs consist of three podomeres that further develop into five segments during development (Singh et al, ). In Bmnotch RNAi embryos, individual podomeres could be clearly identified (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Y‐shaped thoracic legs were reminiscent of a similar biramous phenotype observed in delta RNAi embryos of cricket (Kainz et al, ; Mito et al, ). In normal silkworms, thoracic legs consist of three podomeres that further develop into five segments during development (Singh et al, ). In Bmnotch RNAi embryos, individual podomeres could be clearly identified (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…E). The deformed and lengthened prolegs were dramatically distinct from the normal counterparts, which are small non‐segmented protrusions (Singh et al, ). The unseparated proleg terminated in a central planta that was bordered by a row of sclerotized crochets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, BmDll was shown to be present in the proleg primordial tips in silkworm [35]. Since the E dl mutant possesses degenerated prolegs without distal limb structures on A3, we performed whole-mount BmDll antibody staining to detect whether its expression pattern was changed.…”
Section: Resultsmentioning
confidence: 99%
“…In silkworm, BmDll induces proleg development with the absence of Bmabd-A in the proleg primordia during early embryogenesis, thus it is suggested that BmDll is suppressed by Bmabd-A [16, 35]. However, the interaction between Hox and Dll in distal appendage structures development is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation